THE ESSENCE AND PRACTICAL VALUE OF PEDAGOGICAL CONDITIONS AND PRINCIPLES FOR THE EDUCATIONAL TRAINING OF FUTURE MASTERS IN LEGAL SCIENCES TO THE TEACHING ACTIVITY - Bessmoly, Ye. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
In order to develop the core element of professional training (knowledge, skills and abilities) the system of pedagogical conditions and principles (overall didactical and specific), that include the peculiarities in performing teaching activities while training lawyers.The core of this system is formed by the general didactical principles: a systematic and consequent approach, scientific methods in terms of training; a dominant-motivational mindset; availability of training; clear examples in the course of the training process; consciousness and an active approach in the course of the training process; the solidity of knowledge, skills and abilities; the inclusion of peculiarities related to the individual and his age.The peculiar principles that determine the essence of a law pedagogue in the currently developed situation, among these principles there’re the following: the principle of the dominant –motivational mindset, the principle of an individual approach, the principle of variable rhythmical training, the principle of strict determination and setting of time limits for the professional actions of a teacher; the principle of additional psychological pressure based on the main psycho-physiological pressure; the principle of emotional training.Among the organizational-pedagogical conditions there’re the following: providing of professional motivation to the future masters; the assurance of the training to be oriented at the professional and psychological imprints of the law pedagogue; active use of the informational environment of the educational facility; the introduction of interactive methods in order to form the pedagogical culture of the future masters in law.The peculiarity of training of future lawyers challenges the teacher of law disciplines with a number of requirements as for the personality of the teacher, which in pedagogical science are defined as professionally significant personal qualities, and the scientific basis for the formation of these qualities are pedagogical principles and organizational and pedagogical conditions.To form the content of vocational training (knowledge, skills and abilities), we need a system of pedagogical conditions and principles (general and specific), that take into account all the peculiarities and specifics of teaching lawyers. As a basis of this system we put general didactic principles: systemicity and consistency; scientific knowledge in learning; dominant-motivational attidude; learning accessibility; visibility in learning; awareness and learning activity; strength of knowledge, skills and abilities; taking into account individual and age-specific features. Specific principles that reflect the essence of the teacher of law disciplines in modern conditions of development include: the principle of dominant-motivational attitude; the principle of individual approach in learning; the principle of multi-directional rhythmic training; principle of strict regulation and time limitation of professional actions of the teacher; the principle of additional psychological charge on the base of psycho-physiological stress; the principle of emotionality in learning.General dictatic principles are the basis for studying all disciplines, and also should regulate the organizational foundations of the educational process at different levels. Principles are closely related to the laws of learning and reflect didactic laws. On the basis of general didactic principles, the principles of professional methodology are developed.One of the mentioned directions of realization of the preparation of the future masters in jurisprudence for teaching activities is the introduction of interactive forms and methods of teaching that contribute to the expected results, the integration of disciplines of psychological and pedagogical preparation becomes especially important.The organizational-pedagogical conditions include: providing professional motivation for future masters; orientation of training on the profession and psychograms of the teacher of law disciplines; use of information environment of educational institution; the introduction of interactive methods for the formation of the pedagogical culture of future masters of jurisprudence.
Keywords: pedagogical principles, pedagogical conditions, professional training of lawyers, master's degree